Child development : principles and perspectives - Cook, Joan Littlefield; Cook, Greg (Greg L.) (Boston, Mass. ; London : Allyn and Bacon, 2009)
Child Development: Principles and Perspectives, 2E shows students the power of developmental research in practice! The topically-organized Child Development, Second Edition combines streamlined coverage with an application-driven active learning system. Cook and Cook focus students on how they can promote positive child development by putting the science to work outside of the classroom. The approach recognizes that the majority of students enrolled in the child development course will likely interact in the future with children as educators, medical professionals, social workers, counselors, or as parents. For this reason, the authors punctuate each chapter with numerous applications, including interviews with a real parent (or child) and a real professional who in some way depends upon child development research. Child Development is supported by the new and improved MyDevelopmentLab, an exciting learning and assessment tool designed to increase student success in the classroom, and provide instructors with every resource needed to teach and administer their course. The latest version of MyDevelopmentLab features Virtual Child. This interactive simulation offers students the opportunity to act as a parent and raise a virtual child.
Exploring child development -- Heredity and the environment -- Prenatal development and birth -- Physical development : body, brain, and perception -- Cognitive development : Piagetian and sociocultural views -- Information processing : the development of memory and thought -- Intelligence and academic skills -- Language development -- Attachment, temperament, and emotion -- The development of self and gender -- Moral development -- Peers, play, and popularity -- Families -- Schools, media, and culture.
Includes bibliographical references and indexes.
1
Keywords: Child development